Kinetics of postdiagnosis platelet count with overall survival of pancreatic cancer: a counting process approach. (10th February 2016) - Xiao, Yuanyuan; Xie, Hua; Xie, Zhihui; Shao, Zhenyi; Chen, Wen; Qin, Guoyou; Zhao, Naiqing
Abstract: The association between long‐term variation of postdiagnosis platelets and survival of pancreatic cancer (PC) has never been discussed by using dynamic survival analysis method. In this retrospective study, we analyzed 311 histologically confirmed PC patients identified from a mega population‐based electronic inpatients database from 2012 to 2013 in China. Counting process approach was applied to restructure the original survival data, the association between post‐diagnosis platelet count and overall survival (OS) of PC was evaluated by multiple failure‐time Cox proportional hazards model. After counting process adjustment, multiple failure‐time Cox proportional hazards model revealed that, regardless of the treatment modalities PC patients received, postdiagnosis thrombocytopenia was prominently associated with OS, compared with PC patients with normally ranged platelet count, the HRs ranged from 2.04 (95% CI: 1.14–3.67) to 10.82 (95% CI: 2.63–44.54), and this inverse association was robust based on further sensitivity analysis. On the contrary, the association between thrombocytosis and OS of PC tended to be inconclusive. Our findings suggested that postdiagnosis thrombocytopenia was associated with significantly compromised survival among PC patients from this large retrospective cohort. Underlying mechanisms behind this association should be further investigated. Abstract : Dynamic survival methods are rarely seen in analyzing time‐varying blood indicators and cancer survival. In this study, through the application of counting process approach and the subsequent multiple failure‐time Cox model, we found that among 311 retrospectively determined pancreatic cancer (PC) patients diagnosed between 2012 and 2013, postdiagnosis thrombocytopenia was consistently associated with a compromised overall survival.